KAJIAN TEORITIK EVALUASI PEMBELAJARAN AGAMA ISLAM - Rahmat Lutfi Guefera (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
In general, the condition of Islamic education, both in quality and quantity is less encouraging. There is a big gap between the ideals of education idealized in the Qur'an and the reality that occurs in the people life. In other words, in organizing education carried out by Muslims, there is a very wide gap or gap between the goals of religious doctrine and the reality of practice between mind and fact.